Contribution of CT-Scan Analysis by Artificial Intelligence to the Clinical Care of TBI Patients - Brossard, Clément; Lemasson, Benjamin; Attyé, Arnaud; de Busschère, Jules-Arnaud; Payen, Jean-François; Barbier, Emmanuel L.; Grèze, Jules; Bouzat, Pierre (Frontiers in Neurology, 2021)
The gold standard to diagnose intracerebral lesions after traumatic brain injury is computed tomography (CT) scan. Due to its accessibility and improved quality of images, the global burden of CT-scan is increasing for TBI patients. The recent developments of automated determination of traumatic brain lesions and medical-decision process using artificial intelligence (AI) represent opportunities to help clinicians in screening more patients, identifying the nature and volume of lesions and estimating the patient outcome. This short review will summarize what is ongoing with the use of AI and CT-scan for patients with TBI.